1991
DOI: 10.1093/carcin/12.6.985
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effects of 2-acetylaminofluorene on hepatic foci development and cell proliferation in rats

Abstract: Dose-dependent development of pre-neoplastic liver cell foci induced by 2-acetylaminofluorene (2-AAF) was investigated in relation to cell-proliferative activity. Male F344 rats were initially given a single i.p. injection of diethylnitrosamine (DEN, 200 mg/kg) and starting 2 weeks later received diets containing 2-AAF at dose levels of 150, 100, 60, 45, 35 or 30 p.p.m., 500 p.p.m. phenobarbital (PB) or basal diet as a control for 6 weeks. Two-thirds partial hepatectomy (PH) was performed at week 3. The rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Using 3 hepatocarcinogens, 2-AAF, 3'-Me-DAB, and DL-ethionine, at 3 dose levels, it was clearly indicated that the degree of induction of GST-P-positive foci and nodules in the medium-term bioassay system corresponds with the incidences of hepatocellular carcinomas as revealed by longterm carcinogen exposure (35). A precise dose-response study was also performed using 2-AAF as a model compound to compare the results with the EDO, mega-mouse study of hepatocarcinogenicity (44), and the reliability of our system was again confirmed (51 4 carcinogenic peroxisome proliferators, and tamoxifen did not enhance development of GST-P-positive foci development. With regard to the carcinogenicity of nonmutagenic peroxisome proliferators, it is important to remember that they depress GST-P expression, and the lesions associated with their hepato- (Table III).…”
Section: Marker Lesionsmentioning
confidence: 91%
“…Using 3 hepatocarcinogens, 2-AAF, 3'-Me-DAB, and DL-ethionine, at 3 dose levels, it was clearly indicated that the degree of induction of GST-P-positive foci and nodules in the medium-term bioassay system corresponds with the incidences of hepatocellular carcinomas as revealed by longterm carcinogen exposure (35). A precise dose-response study was also performed using 2-AAF as a model compound to compare the results with the EDO, mega-mouse study of hepatocarcinogenicity (44), and the reliability of our system was again confirmed (51 4 carcinogenic peroxisome proliferators, and tamoxifen did not enhance development of GST-P-positive foci development. With regard to the carcinogenicity of nonmutagenic peroxisome proliferators, it is important to remember that they depress GST-P expression, and the lesions associated with their hepato- (Table III).…”
Section: Marker Lesionsmentioning
confidence: 91%
“…Furthermore, this bioassay was recommended as an acceptable alternative to the long-term rodent carcinogenicity test at the Fourth International Conference on Harmonization 16 . Since the required time is relatively short and the quantitative measurement of GST-P positive foci is very sensitive, it is relatively easy to conduct studies with many different doses of chemical to assess dose-dependence of carcinogenic potency 18,19 . In particular, a Japanese research group has been approaching this very important issue using this assay system 20 .…”
Section: Discussionmentioning
confidence: 99%
“…With the liver foci assay, false negative results are estimated to occur for about 10% of hepatocarcinogenic agents (Tiwawech et al 1991). As a consequence, the missing significant increase in the number and size of g-glutamyltranspeptidase-positive foci in the liver of rats given 100 and 500 mg/kg/week flutamide for 6 successive weeks indicates that this drug is most likely not capable of acting as initiator of liver tumours.…”
Section: Discussionmentioning
confidence: 99%